Morphological Study of Liver in Rats With Toxic Hepatitis After Application of Cryopreserved Human Cord Blood Serum - Goltsev, Anatoliy N.; Falko, Oksana V.; Volina, Victoria V.; Lipina, Olga V.; Prokopyuk, Olga S.; Gulevsky, Oleksandr K. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 014–018